Evaluasi Tata Kelola Teknologi Informasi Dinas Komunikasi dan Informatika (Diskominfo) Kota Batu Menggunakan Framework COBIT 4.1 Domain Plan and Organise (PO) dan Acquire and Implement (AI) - Fanistya Dias Afrilia; Suprapto Suprapto; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dinas Komunikasi dan Informatika (Diskominfo) of Batu City is a government agency which focused on informatic technology. In this department, planning and implementation of an IT are handled by the ICT Infrastructure Network and Applications department. From the observations, interviews, and questionnaires, this department have some several problems in management of IT governance asynchronous between planning and implementation of budget management plan, and lack of human resources training for IT users. COBIT 4.1 framework are used in this research, and we focus on the Plan and Organize (PO) and Acquire and Implement (AI) domains. From the measurement of maturity level, we got the average maturity level for PO and AI domains are 1.89 and 1.61. From that, we made some recommendations for improvements based on that result. One of the recommendations is to make an Standard Operating Procedure (SOP) documents in all services that they handled.